PENGARUH KOMUNIKASI EFEKTIF TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PELAJARAN EKONOMI SMAN 2 SUNGAI RAYA - Alfajri, Alfajri; Sulistyarini, Sulistyarini; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study entitled, The effect of effective communication on the thinking ability of students of class 10 IPS SMA 2 Sungai Raya. The problem in this study was whether there was on students' critical thinking abilities. The purpose of this research was whether there was an effective communication on students' critical thinking abilities. The method used in this research was a descriptive method with the form of related research studies. The sample in this study amounted to 50 students of class 10 IPS. The Data obtained using indirect observation techniques with data the collection tools in the questionnaire and documentary studies with the form of a photo. The results of the studies show that effective communication the teacher proven to give the stimulus the student the active. Furthermore, critical thinking carried out by students has well proven active students in the learning process. Based on data analysis techniques using the t-test obtained t count > t table (2.936 > 2.010), then Ha was accepted. so it can be concluded that there significant effect between effective communication on students critical thinking skills in class 10 SMA 2 Sungai Raya.Keywords: Communication Effective, Student Critical Thinking